Effectiveness of bioengineering methods of water erosion control in Tarka valley versant , Niger Republic (2012)
Erosion problem is recognized as a serious threat to human beings, forestry and agricultural activities in the rural areas of Niger Republic. The effectiveness of three Bio-engineering methods of water erosion control in the degraded land of two villages in Bouza local government area, of the Niger Republic was assessed. These two villages are highly susceptible to water erosion. The three methods of erosion control used were wall of stone, Trench and Demi-Lune. Trees and herbaceous plants were then introduced to the reclaimed land to green up the environment. After generation, data collected include rate of soil cover by herbaceous vegetation, inventory of woody and herbaceous vegetation, stand density and the survival rate of planted trees. Result showed high biomass production and great density of herbaceous species of different families with the highest species frequency being Gramineae. The total biomass production for the two sites was estimated at about 413.15 and 461.12 tons for Babarangua and Kougouptache respectively. Statistical analysis showed that the site has no significant influence on biomass production while the technique adopted exhibit significant influence on production at the same level of probability. The wall of stone technique gave the best result in herbaceous production while the trench and Demi-lune technique ensure good rate of tree survival for the planted trees. The three methods were effective in erosion control in two sites.